The problem of detecting long-term forgetting: Evidence from the Crimes Test and the Four Doors Test. (January 2019) - Baddeley, Alan; Atkinson, Amy; Kemp, Steven; Allen, Richard
Abstract: While most individuals who have problems acquiring new information forget at a normal rate, there have been reports of patients who show much more rapid forgetting, particularly comprising a subsample of patients with temporal lobe epilepsy. Currently available tests are generally not designed to test this since it requires multiple different tests of the same material. We describe two tests that aim to fill this gap, one verbal, the Crimes Test, the other visual, the Four Doors Test. Each test involves four scenes comprising five features. In each case, this allows four tests of 20 different questions to be produced and used at four different delays. Two experiments were run, each comprising a multi-test condition in which immediate testing was followed by retesting after 24 h, one week and one month, and a second condition involving a single test after one month. Both the visual and verbal tests showed clear evidence of forgetting in the single test condition, together with little evidence of forgetting in the multi-test conditions. We suggest that the testing of individual features encourages participants to remember the whole episode which then acts as a further reminder. Further research is needed to decide whether this serendipitous lack of forgetting in healthy individuals (decelerated long-term forgetting) will provide an ideal test of accelerated long-term forgetting by avoiding the danger of floor effects, or whether it will simply prove to be a further complication. Theoretical implications are discussed, as well as possible ways ahead in further investigating the surprisingly neglected field of long-term forgetting.